COMPARING COMMUNITY-BASED AND EMR RECRUITMENT FOR ENGAGING OLDER MINORITY ADULTS: RESULTS FROM TAKE HEART. (11th November 2018) - Ramsay, J; Hogan, C; Courser, R; Edwards, D; Janevic, M; Connell, C
Abstract: Recruiting older adults for behavioral interventions is challenging, particularly those from racial/ethnic minority and low SES communities. Thus, it is critical to share knowledge about effective strategies for engaging this population in research. This presentation describes the recruitment process for Take Heart, a randomized controlled trial (RCT) of an evidence-based heart disease self-management program for older adults in Detroit. We compare community-based (e.g., flyer distribution, information sessions, health fairs) and electronic medical record (EMR) recruitment in a low SES African American community. We also present recruitment challenges unique to a RCT given the requirement for a control condition. Of the 1, 155 eligible participants, 63% were identified via community-based recruitment, 37% via EMR. Of participants recruited via community-based methods, 52% enrolled in the study, versus 9% of those recruited by EMR. Overall, 355 (30%) of all eligible and interested participants enrolled in Take Heart. The most successful recruitment methods were flyer distribution and information sessions. Results highlight the effectiveness of community-based methods over recruitment using EMR. Employing a community health worker from Detroit enhanced recruitment, and the availability of transportation services to attend Take Heart educational sessions further enabled potential participants to enroll in the study. Contrary to expectation, participants readily accepted assignment to the control group. Although community-based methods require significant staff time and effort, Take Heart provides an example of their value in engaging older adults most in need of chronic disease self-management programs.